A case report of brown tumor in a patient with chronic renal failure and renal cell carcinoma. Issue 4 (29th November 2017) - Liu, Yong‐Jun; Frauenhoffer, Elizabeth E.; Walker, Eric; Williams, Nicole C.
Abstract : We report a case of a 72 year old male with hyperparathyroidism secondary to end stage diabetic renal disease and coexisting bilateral chromophobe renal cell carcinomas. The patient presented with back and groin pain, right pelvic hemorrhage, and multiple lytic bone lesions concerning for metastatic renal cell carcinoma. Fine needle aspiration cytology demonstrated benign appearing osteoclasts and spindled cells. A concurrent core biopsy showed foci of spindled cell proliferation populated by osteoclast‐like giant cells with stromal hemorrhage without evidence of metastatic carcinoma. The cytologic and histologic findings, in correlation with the clinical history, radiographic features, markedly increased parathyroid hormone levels and other serologic studies, were diagnostic of the reactive lesion seen in brown tumor of hyperparathyroidism secondary to chronic renal failure.